Evaluasi Pengelolaan Sampah Oleh Badan Lingkungan Hidup Kabupaten Kampar - Fadli Farhan, Adhe; Elfi Istiqoh, Akhdiva; Harmain, Irfan; Asyikin, Azrul (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study evaluates the waste management system implemented by the Kampar Regency Environment Agency in Kubang Jaya Village. This study aims to assess the effectiveness, efficiency, adequacy, responsiveness, and accuracy of waste management policies. A qualitative approach is used, utilizing interviews, observations, and document analysis to collect data. The findings show that waste management remains suboptimal due to limited waste collection, inadequate facilities, and budget limitations. The absence of routine waste transportation and inadequate community participation further exacerbate this problem. Additionally, the lack of a structured waste management system results in reactive rather than preventive action. Waste collection is only available in certain areas, so many households handle waste disposal independently. The absence of waste sorting at the source and the limited capacity of waste disposal facilities further complicate waste management efforts. The findings also reveal that government responses are often slow, with the accumulation of waste leading to environmental and health hazards. Although some initiatives, such as community-based waste management programs and waste banks, have been introduced, their implementation has remained inconsistent. The study highlights the need for increased budget allocation, infrastructure improvements, and increased community engagement to ensure sustainable waste management. Collaborative efforts between governments, the private sector, and local communities are essential to develop an integrated waste management system. Future research should expand its scope to other villages to provide a more comprehensive analysis of waste management throughout Kampar Regency. Overcoming these challenges requires long-term policy planning, regulatory enforcement, and public awareness campaigns